2015
DOI: 10.4238/2015.june.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on the risk factors of urinary calculus in Uyghur children in the Kashi region

Abstract: ABSTRACT. The incidence of urinary calculus (UC) is very high in Uyghur children in the Kashi region of Xinjiang, China, which seriously affects the growth and life quality of these children. This study was aimed at investigating the risk factors of UC in Uyghur children in Kashi region. One hundred fifteen Uyghur children (age <7 years) with UC who were treated in First People's Hospital in Kashi were enrolled in the case group. A 1:1 case-control study with a questionnaire was performed. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It is widely accepted that paediatric urolithiasis is associated with metabolic disorders; inherited problems; UTI; malnutrition; dehydration; and dietary habits, such as high salt and high animal protein diets . In agreement, the present study showed that BMI, UTI, family history of urolithiasis, and excessive sweating were risk factors for stone formation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is widely accepted that paediatric urolithiasis is associated with metabolic disorders; inherited problems; UTI; malnutrition; dehydration; and dietary habits, such as high salt and high animal protein diets . In agreement, the present study showed that BMI, UTI, family history of urolithiasis, and excessive sweating were risk factors for stone formation.…”
Section: Discussionsupporting
confidence: 89%
“…A nationwide epidemic of urolithiasis occurred amongst children 10 years ago in China, which was found to be caused by drinking melamine in powdered‐milk formula, and no new cases appeared after prohibiting the production and drinking of this kind of milk . However, urolithiasis is still common amongst the Uyghur paediatric population . The Uyghur live in Northwestern China, with a population of 10 million .…”
Section: Introductionmentioning
confidence: 99%
“…As literatures reported, a high percentage of upper urinary tract stones was associated with metabolic disturbance, which may stem from dietary patterns [13]. A epidemiological survey found the cow milk with higher Ca, P and other mineral contents was long-term fed to infants in the Kashi of Xinjiang, which may lead to an disorder of Ca and P metabolism, and then promoting the development of urolithiasis [41]. Also, more epidemiological investigations indicated high-protein, purine-rich food (such as animal offal, beef and mutton) and excessive intake of dietary sodium salt are common dietary patterns of Uyghur people [7,15,41].…”
Section: Discussionmentioning
confidence: 99%
“…A epidemiological survey found the cow milk with higher Ca, P and other mineral contents was long-term fed to infants in the Kashi of Xinjiang, which may lead to an disorder of Ca and P metabolism, and then promoting the development of urolithiasis [41]. Also, more epidemiological investigations indicated high-protein, purine-rich food (such as animal offal, beef and mutton) and excessive intake of dietary sodium salt are common dietary patterns of Uyghur people [7,15,41]. A transient excessive consumption of high-protein and high-purine food could increase endogenous acid production and urinary excretion of calcium, oxalate, and uric acid, decreasing the excretion of citrate and increasing acid load in the body, and then decreasing urine pH and further resulting in the development of UA/ CaOx stones [7,13].…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of urolithiasis has been associated with variations in its epidemiology like change in age, sex distribution of the disease and also changes in terms of type and location of the calculi. [1,2,3] Present study describes clinical profile of urolithiasis patients visiting Radiodiagnosis department of a tertiary care hospital in Solapur district of Maharashtra state in India.…”
Section: Introductionmentioning
confidence: 99%